GAMBARAN PENGGUNAAN OBAT TRADISIONAL DI DESA CIKERIS PURWAKARTA - Lina Aliyani, Lina Aliyani Mardiana; Fatwa, Dini Noer; Ramadhina, Aisyah Salsabila (Jurnal Buana Farma, 2024)
The use of traditional medicine as an alternative treatment is widely practiced in various regions in Indonesia, including Cikeris Village, Purwakarta. This study aims to determine the description of the use of traditional medicine in Cikeris Village, including the characteristics of respondents, types of traditional medicine used, and the level of community knowledge about traditional medicine. The study used a quantitative descriptive method by distributing questionnaires to 97 respondents. The results showed that 52.6% of respondents were male, the majority were aged 25-44 years (56.7%), had a high school education (67.0%), and worked as farmers (28.9%). A total of 64.9% of respondents used traditional medicine based on information passed down from their parents. The most frequently used traditional medicines were ginger (23.7%), turmeric (20.6%), and beras kencur (10.3%). Packaged products such as Tolak Angin (4.1%) and Kiranti (2.1%) were also found to be used. The level of community knowledge about traditional medicine is quite good, with 82.43% of respondents giving correct answers to the eight statements asked. This study shows that the people of Cikeris Village have good habits and knowledge related to the use of traditional medicine as part of daily treatment.